P-748 Cesarean scar defect does not predict embryo transfer outcomes: A retrospective cohort study. (30th June 2022) - Gale, J; Lanes, A; Corran, B; Bacal, V; Nguyen, V; Shmorgun, D; Singh, S.S; Walker, M
Abstract: Study question: Is the presence of a cesarean scar defect associated with live birth outcomes at the time of embryo transfer? Summary answer: The presence of a cesarean scar defect is not predictive of live birth rates at the time of embryo transfer. What is known already: Cesarean delivery is associated with subsequent impaired fertility, with lower pregnancy and live birth rates and longer inter-pregnancy intervals, compared to patients who delivered vaginally. Studies exploring pregnancy rates after IVF and embryo transfer also suggest lower pregnancy rates among patients with prior cesarean delivery. A postulated mechanism by which a prior cesarean delivery may impact fertility is the cesarean scar defect, and prior studies have shown a possible association between a scar defect and suboptimal outcomes. Study design, size, duration: We retrospectively identified a patient cohort based out of the Ottawa Fertility Centre in Ottawa, Ontario, Canada, between 2013 and 2019. Participants/materials, setting, methods: This retrospective cohort study included 317 patients with a prior cesarean delivery. Embryo transfer outcomes compared between the two groups based on the finding of a cesarean scar defect. The primary outcome was live birth rate, secondary outcomes of positive hCG, clinical intrauterine pregnancy, miscarriage rate. We fit a multivariate log binomial regression model with a priori variables for the primary and secondary outcomes, adjusting for patient and cycle characteristics. Main results and the role of chance: There was no statistically significant difference in live birth rate among patients with a cesarean scar defect compared to those without, 28.0% vs 29.5% respectively (adjusted RR 0.95, 95% CI 0.68-1.35). There was no statistically significant difference in any of the secondary outcomes. Area of the defect and subgroup analysis of fresh vs frozen embryo transfer did not demonstrate any difference. Secondary analysis of patients with retroverted uterus had significantly lower live birth rates compared to those with an anteverted uterus, 17.7% vs 32.4%, respectively (adjusted RR 0.56, 95% CI 0.34-0.91). Limitations, reasons for caution: Although a multivariate log binomial model was used to adjust for clinically relevant confounders, there remains the possibility for residual confounding given the observational nature of our study. Wider implications of the findings: The results of our study suggest that, after adjusting for patient and cycle characteristics, the presence of a cesarean scar defect may not impact live birth outcomes and secondary analysis of the impact of uterine retroversion requires more study. Trial registration number: Not applicable